Pemberdayaan UKM Bhamada English Club dalam Meningkatkan Kemampuan Speaking Bahasa Inggris melalui Aplikasi Duolingo Berbasis Task-Based Learning - Binta Ihtada; Amanda Apriliant (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
English speaking skill is a crucial competence for university students, particularly those involved in student organizations focusing on language development. Members of English clubs are expected to actively use English in academic and organizational contexts; however, many still face challenges related to pronunciation accuracy, fluency, limited active vocabulary, and low confidence. These challenges are often caused by limited structured speaking practice and insufficient integration between digital learning tools and communicative pedagogy.This community service program aimed to enhance the English-speaking skills of members of the Bhamada English Club at Universitas Bhamada Slawi through the utilization of the Duolingo application integrated with a Task-Based Learning (TBL) approach. The program was implemented through three stages: preparation, implementation, and evaluation. Activities included needs analysis, speaking pre-test, guided Duolingo practice focusing on pronunciation and speaking features, task-based speaking activities, and post-test evaluation.The results demonstrated improvements in pronunciation accuracy, speaking fluency, and participants’ confidence in using English orally. The integration of Duolingo as a source of comprehensible input and Task-Based Learning as a communicative output strategy proved effective in enhancing speaking skills. This program indicates that technology-supported task-based instruction can serve as an effective and sustainable model for improving English speaking skills among university students.